2022
DOI: 10.2176/jns-nmc.2022-0055
|View full text |Cite
|
Sign up to set email alerts
|

Dural Arteriovenous Fistula Mimicking a Brain Tumor on Methionine-positron Emission Tomography: A Case Report

Abstract: In this article, we report a case wherein a brain tumor was suspected based on computed tomography and magnetic resonance imaging findings. We made an initial diagnosis of malignant brain tumor based on methionine-positron emission tomography (PET) findings, but the correct diagnosis was dural arteriovenous fistula (DAVF). The patient was a 45-year-old man with DAVF who developed headache. Methionine-PET imaging showed high methionine uptake in the lesion. Although the tumor was strongly suspected from the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The nerve functions of the patient were restored after treatment [12]. Hanyu et al reported the case of a 45-year-old male with a headache and a final angiographic diagnosis of DAVF, although he was initially suspected of having brain malignancy based on the results of positron emission tomography-CT (PET-CT) and MRI [13]. These cases have some similarities.…”
Section: Discussionmentioning
confidence: 99%
“…The nerve functions of the patient were restored after treatment [12]. Hanyu et al reported the case of a 45-year-old male with a headache and a final angiographic diagnosis of DAVF, although he was initially suspected of having brain malignancy based on the results of positron emission tomography-CT (PET-CT) and MRI [13]. These cases have some similarities.…”
Section: Discussionmentioning
confidence: 99%